Societal responsibility of artificial intelligence : towards an ethical and eco-responsible AI - e uthor ([Place of publication not identified] : John Wiley & Sons, Inc., 2021)
The digital world is characterized by its immediacy, its density of information and its omnipresence, in contrast to the concrete world. Significant changes will occur in our society as AI becomes integrated into many aspects of our lives. This book focuses on this vision of universalization by dealing with the development and framework of AI applicable to all. It develops a moral framework based on a neo-Darwinian approach - the concept of Ethics by Evolution - to accompany AI by observing a certain number of requirements, recommendations and rules at each stage of design, implementation and use. The societal responsibility of artificial intelligence is an essential step towards ethical, eco-responsible and trustworthy AI, aiming to protect and serve people and the common good in a beneficial way.
Societal and Moral Questioning Around AI and Its Ecosystem -- The Ethical Approach to AI -- Ethical Framework Associated with AI -- Anticipation Around Artificial Consciousness -- Conclusion -- Appendices. Ethical Charter of Using AI in Judicial Systems and Their Environment -- Practical Recommendations of the CNIL Regarding the Ethics of Algorithms -- OECD Recommendation on AI -- Questions Concerning the Application of Ethical Standards -- CERNA Recommendations on Machine Learning -- Reasons for a "Digital Divide" -- Holberton-Turing Oath -- Report Proposals: "For a Controlled, Useful and Demystified Artificial Intelligence" -- List of Abbreviations -- References -- Index -- Other titles from iSTE in Health Engineering and Society
Includes bibliographical references and index.
Online resource; title from PDF title page (SpringerLink, viewed June 21, 2021).
John Wiley and Sons
Keywords: Artificial intelligence -- Moral and ethical aspects; Intelligence artificielle -- Aspect moral; Artificial intelligence -- Moral and ethical aspects